ANALISIS TINDAK TUTUR ILOKUSI DALAM CERPEN “INI TENTANG AKU” KARYA PUTU AYUB DALAM BUKU AKU, DIA, DAN MEREKA (SEBUAH KUMPULAN CERPEN) - Iqbal, Nur Aisyah Awaliyah; Mujahidah Nurqalbi; Abdul Haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
As social creatures, humans always use language in daily communication to convey certain intentions. The short story "It's About Me" by Putu Ayub was analyzed to identify the various illocutionary speech acts used. This research uses descriptive qualitative methods through literature review. The results of the analysis showed that illocutionary speech acts such as praise, questions, explanations, entertainment, and advice had mixed effects on recipients. Compliments help break the ice, while questions and explanations can cause discomfort if they touch on sensitive topics. Entertainment and advice provide emotional support and trigger introspection in the recipient. The study revealed that the way of communication and word selection can have a significant impact on recipients in social and emotional contexts